2021
DOI: 10.3390/coatings11080979
|View full text |Cite
|
Sign up to set email alerts
|

Application of Propolis Extract in Gelatin Coatings as Environmentally Friendly Method for Extending the Shelf Life of Pork Loin

Abstract: This study evaluates the effects of gelatin coating enriched with ethanolic propolis extract (PE) at 1%, 2% or 3% (w/v) on the quality parameters of pork meat during storage at 2 °C. Physical (pH, weight loss, color) and chemical parameters (percentage contents of metmyoglobin (MetMb), along with thiobarbituric acid reactive substances (TBARS)) were measured, and microbiological (total aerobic plate count (TAPC)) analysis, as well as consumer evaluation, was carried out every four days during the storage perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…By contrast, chitosan and chitosan/SACC composite coated pork loins showed relatively lower weight losses, which were 8.12% and 7.16% respectively on day 14. On the one hand, the weight loss of pork is associated with water evaporation 40 . Previous studies have demonstrated that chitosan coating is an effective way to prevent the weight loss of pork loins by acting as a barrier to water vapour 16,41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, chitosan and chitosan/SACC composite coated pork loins showed relatively lower weight losses, which were 8.12% and 7.16% respectively on day 14. On the one hand, the weight loss of pork is associated with water evaporation 40 . Previous studies have demonstrated that chitosan coating is an effective way to prevent the weight loss of pork loins by acting as a barrier to water vapour 16,41 .…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the weight loss of pork is associated with water evaporation. 40 Previous studies have demonstrated that chitosan coating is an effective way to prevent the weight loss of pork loins by acting as a barrier to water vapour. 16,41 In the present study, results revealed chitosan/SACC composite coating was more effective in preventing weight loss of pork loins in comparison with chitosan coating.…”
Section: Antioxidant Activity Of Coating Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin is a natural biopolymer obtained from collagen under controlled hydrolysis. It has well-known properties for drug delivery, wound healing, and tissue regeneration applications [1][2][3][4][5][6][7]. Despite several advantages in biomedical engineering and regenerative medicine, gelatin has some major problems including melting at temperatures about or above 37 • C in water and hardening into gel at room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of propolis added to the gelatin coating on shelf life was also observed. In addition to the antioxidant properties of the coating, the inhibitory effects on the growth of microorganisms were also observed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%